Using Quality and Accreditation standard in performance improvement of education institutions: بحث تطبيقي في كلية الهندسة جامعة بغداد (Journal of Accounting and Financial Studies ( JAFS ), 2019)
enjoyed the process of the development of higher education institutions attention of most countries of the world and to reconsider its objectives and programs and administrative and organizational structures, and it was the most important development of the application of Quality Assurance and Accreditation Standards (QAAS) tools, as the aim of these tools to the application of advanced with a far-reaching impact on all of the disciplines in the organization methods education that contribute, and plays a performance audit an important role in verifying the extent to which carried out these institutions activities or programs effectively and efficiently, economic, There are a number of objectives for the search of the most important attempt to measure and evaluate the performance of educational institutions using citing quality assurance and accreditation of academic standards, is achieved through the adoption of a proposal to audit the performance of educational institutions program indicators.The research has come to a group of the most important conclusions are: There are some models and experiences of some countries in the application of academic accreditation in institutions of higher education system, it can be guided by the idea of the establishment of a council for academic accreditation as a mechanism appropriate follow up the quality of higher education, in line with international standards. There is a close relationship between quality assurance and academic accreditation in achieving the efficiency and effectiveness of performance.In light of the above research found a set of recommendations, including: The need to adopt criteria and indicators for Quality Assurance and Accreditation When you check the institution's performance because it represents the best alternative for measuring the level of efficiency in the educational process and effectiveness in achieving the objectives, as well as the universality of these standards and the content on the indicators of quality that are essential to improve performance.